Nanocrystalline Fe-Fe2O3 particle-deposited N-doped graphene as an activity-modulated Pt-free electrocatalyst for oxygen reduction reaction - Dhavale, Vishal M.; Singh, Santosh K.; Nadeema, Ayasha; Gaikwad, Sachin S.; Kurungot, Sreekumar (Nanoscale, 2015)
The size-controlled growth of nanocrystalline Fe-Fe2O3 particles (2-3 nm) and their concomitant dispersion on N-doped graphene (Fe-Fe2O3/NGr) could be attained when the mutually assisted redox reaction between NGr and Fe3+ ions could be controlled within the aqueous droplets of a water-in-oil emulsion. The synergistic interaction existing between Fe-Fe2O3 and NGr helped the system to narrow down the overpotential for the oxygen reduction reaction (ORR) by bringing a significant positive shift to the reduction onset potential, which is just 15 mV higher than its Pt-counterpart. In addition, the half-wave potential (E-1/2) of Fe-Fe2O3/NGr is found to be improved by a considerable amount of 135 mV in comparison to the system formed by dispersing Fe-Fe2O3 nanoparticles on reduced graphene oxide (Fe-Fe2O3/RGO), which indicates the presence of a higher number of active sites in Fe-Fe2O3/NGr. Despite this, the ORR kinetics of Fe-Fe2O3/NGr are found to be shifted significantly to the preferred 4-electron-transfer pathway compared to NGr and Fe-Fe2O3/RGO. Consequently, the H2O2% was found to be reduced by 78.3% for Fe-Fe2O3/NGr (13.0%) in comparison to Fe-Fe2O3/RGO (51.2%) and NGr (41.0%) at -0.30 V (vs. Hg/HgO). This difference in the yield of H2O2 formed between the systems along with the improvements observed in terms of the oxygen reduction onset and E-1/2 in the case of Fe-Fe2O3/NGr reveals the activity modulation achieved for the latter is due to the coexistence of factors such as the presence of the mixed valancies of iron nanoparticles, small size and homogeneous distribution of Fe-Fe2O3 nanoparticles and the electronic modifications induced by the doped nitrogen in NGr. A controlled interplay of these factors looks like worked favorably in the case of Fe-Fe2O3/NGr. As a realistic system level validation, Fe-Fe2O3/NGr was employed as the cathode electrode of a single cell in a solid alkaline electrolyte membrane fuel cell (AEMFC). The system could display an open circuit voltage (OCV) of 0.73 V and maximum power and current densities of 54.40 mW cm(-2) and 200 mA cm(-2), respectively, which are comparable to the performance characteristics of a similar system derived by using 40 wt% Pt/C as the cathode electrode.